The Early Years Child Well-Being and the Role of Public Policy - Inter-American Development Bank; Schady, Norbert (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
This book is open access under a CC BY-NC-ND 3.0 IGO license.  The Early Years analyzes the development of Latin American and Caribbean children and makes a compelling case for government intervention in what is instinctively a family affair. Spending on effective programs for young children is an investment that, if done well, will have very high returns, while failure to implement such programs will lower the returns on the hefty investments being made in primary, secondary, and higher education. Policies for young children belong at the core of a country's development agenda, alongside policies to develop infrastructure and strengthen institutions. However, if the services provided (or funded) by governments are to benefit children, they must be substantially better than what is currently being delivered in the region. This book offers suggestions for improving public policy in this critical area.